Caracterização agronômica e físico-química de linhagens de pimenta (Capsicum chinense Jacq.) - Giro, Pedro Henrique (Universidade Federal de São Carlos, 2025)
Peppers of the genus Capsicum hold significant economic and cultural importance in Brazil, being widely consumed across all regions, with specific peculiarities in each state. In addition to the domestic market, there is substantial demand abroad, particularly in Asia, the world's largest consumer of this product. Given this scenario, agronomic characterization and the development of new C. chinense cultivars are essential, especially considering that only about 70 cultivars are currently registered in the National Cultivar Registry (RNC). In this context, the present study aimed to evaluate, among the selected lineages, those with commercial potential by characterizing, from agronomic and physicochemical perspectives, nine F5 lineages of Capsicum chinense from the Germplasm Bank of the Federal University of São Carlos, compared to the commercial cultivar 'Dedo-de-moça.' The experiment was conducted in a protected environment using a randomized block design, with three replicates and four plants per plot, totaling 10 treatments. Evaluations were based on quantitative criteria and qualitative descriptors, as well as physicochemical and sensory analyses. Data were subjected to analysis of variance (ANOVA), followed by the Scott-Knott test (p < 0.05). Among the results, the F5 2027-3P Pl.1 lineage stood out, exhibiting the highest yield (8.35 t/ha) and ideal traits for preserves, condiments, and dehydration—such as thinner flesh and smaller fruit size, attributes that favor faster absorption of pickling liquids and more efficient dehydration. Conversely, the F5 2027-3P Pl.2 lineage showed the second-highest yield (7.71 t/ha) and proved more suitable for fresh consumption and sauce production due to its thicker flesh and larger fruit size compared to other lineages. Additionally, it received the highest sensory evaluation score (8.2/10) in consumer preference tests. Both lineages demonstrate potential to advance the genetic improvement of C. chinense, meeting diverse demands of the market and food industry.
Agronomic and physicochemical characterization of pepper lines (Capsicum chinense Jacq.)
Keywords: Caracterização agronômica; Horticultura; Melhoramento genético; Olericultura; Produtividade; Agronomic characterization; Horticulture; Genetic improvement; Olericulture; Productivity; CIENCIAS AGRARIAS::AGRONOMIA